Role of green intellectual capital and company size on business sustainability - Setu Setyawan; Ahmad Juanda; Lia Candra Inata (Journal of Innovation in Business and Economics, 2022)
This study aims to test and analyze the influence of green intellectual capital and company size on business sustainability. The selection of samples was conducted by purposive sampling under the objectives of this study, namely mining companies registered in IDX from 2017-2020. The findings of this study show that green human capital and green structural capital have a significant effect on business sustainability, while green relational capital does not affect business sustainability. In addition, company size has a positive impact on business sustainability. By examining the factors that affect sustainability, this study paves the way for further investigation of this topic with a set of micro and macro variables. This research provides insight into the disclosure of green intellectual capital to business sustainability. The GIC research in Indonesia has been claimed that it has not been widely researched. Accordingly, this research seems to be preliminary. This research also considers the current context of the era of agility and hybrid cloud and the increasing competition in the advanced industry. The company is likely to try to find a strategy to maintain the sustainability of its business.